Письменность Великого княжества Литовского как источник лексических заимствований в других славянских языках - Павловна Гарбулъ, Людмила (Slavistica Vilnensis, 2010)
The article examines the history of the following words found in Russian chancery language (diplomatic correspondence) of Muscovite Russia of the first half of the 17th century: voloka ‘lot and land measure (about 16,8-21 hectare) in the Great Duchy of Lithuania and in the West part of Muscovite Russia’, vypustoʃьyti ‘devastate’, vyrazumeti ‘understand, comprehend; clear up, get to know’, naruʃьyvati ‘break’ and naruʃьytisia ‘be/get broken’. The author aims at proving that these intraslavonic derivates are interslavonic lexical loan-words from the written languages of the Great Duchy of Lithuania in the other Slavonic languages: Polish (wypustoszyć, wyrozumieć, naruszyć się) and Russian (voloka, vypustošyti, vyrazumeti, narušyvati, narušytisia) and retraces further fate of these words in all contacting languages.